Konsep Kedaulatan Dalam Islam: Analisis Metodologi Dalam Islam Terhadap Sistem Ketatanegaraan - Nahla Mujibah; Rahmayana; Naural; Kurniati (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This research aims to analyze the concept of sovereignty in Islam, its implementation, and impact on the modern state system. This study uses normative legal research methods with contextual, comparative, historical, and library research approaches. Data sources are obtained from the Quran, Hadith, fiqh siyasah literature, and various journals and books relevant to the concepts of sovereignty and state administration. The results show that the concept of sovereignty in Islam places sharia as the highest source of law, while the exercise of power is exercised by humans through the principles of deliberation, justice, trustworthiness, and welfare. In the modern state system, the implementation of sovereignty is realized through democratic mechanisms, the rule of law, constitutionalism, the division of powers, and public participation in government. This implementation has had positive impacts in the form of strengthening democracy, increasing political participation, protecting human rights, and creating a more accountable government. However, its implementation still faces challenges such as low public political awareness, the dominance of elite groups, and the influence of globalization and technological developments. Therefore, it is necessary to strengthen the values of justice and the welfare of the people so that the concept of justice can be implemented effectively in realizing a democratic and just state system.